Indigenous Perspectives on Sacred Natural Sites: Culture, Governance and Conservation - Liljeblad, Jonathan; Verschuuren, Bas (Routledge, 2018)
Introduction: Indigenous voice and indigenous sacred sites, promoting diverse perspectives in a global discourse / Jonathan Liljeblad -- Identity and embodying the sacred -- Giving voice to the sacred Black female body in takayna country / Jennifer Evans -- Defending the sacred through plant knowledge / Susan Leopold -- Imagine Kanaloa Kaho'olawe / Davianna Pomaika'i McGregor -- Resistance, advocacy and perseverance -- Kondhs resistance movement to save sacred Niyamgiri, Odisha / Annapurna Devi Pandey -- Human rights law and the protection of sacred sites and territories : a case study of the Bethany Griqua community in South Africa / Lesle Jansen and Ademola Oluborode Jegede -- Taos Pueblo Blue Lake : a legacy of cultural perseverance / Vernon Lujan -- The sacred in intangible heritage and education -- The crocodiles of Fesawa : sacred sites and rituals in a changing context in Southern East Timor / Brunna Crespi, Anacleto Amaral and Clementino Amaral -- Maghee : a case study of indigenous Tharu cultural heritage for democratic practice and STEM education / Bhaskar Upadhyay, Mahesh Tharu Chaudhary, Dinesh Gautam and Baliram Tharu -- Recognition and preservation of the sacred in place -- Wirikuta : sacred heart of Mexico : Pueblo Wixárika (Huichol) / Anaid Paola Velasco Ramirez, Ursula Garzón Aragón, Andrea Ulisse Davide Cerami, and Santos De La Cruz Carillo -- Hongan di Pa'ge : the sacredness and realism of terraced landscape in Ifugao culture, Philippines / Marlon Martin, Stephen Acabado and Raymond Macapagal -- Perpetuation is the key to preservation : encouraging local development and valuing indigenous culture as the sole bastion against Bagan's museification / Bérengère Boüan and Kathy Khine -- Protecting our sacred water : cenote conservation in the Maya area of Yucatan, Mexico / Yolanda Lopez-Maldonado.